2022
DOI: 10.3390/ijms23168914
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the SWEET Gene Family in Longan (Dimocarpus longan) and the Role of DlSWEET1 in Cold Tolerance

Abstract: Sugars will eventually be exported transporters (SWEET), a group of relatively novel sugar transporters, that play important roles in phloem loading, seed and fruit development, pollen development, and stress response in plants. Longan (Dimocarpus longan), a subtropic fruit tree with high economic value, is sensitive to cold. However, whether the SWEET gene family plays a role in conferring cold tolerance upon longan remains unknown. Here, a total of 20 longan SWEET (DlSWEET) genes were identified, and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
10
1
Order By: Relevance
“…At present, there is no report on the specific bHLH gene known to regulate salt gland development in other halophyte species, making it difficult to find homologous and unique genes for salt gland development. Most studies about L. bicolor remain at the developmental level of the epidermal structure of heterologous overexpression plants [ 20 , 46–48 ], and there has been little research into the roles of L. bicolor genes in salt gland generation and salt discharge. Earlier, we confirmed by in situ hybridization that the L. bicolor gene Lb1G04899 ( LbbHLH ) is expressed in salt glands [ 29 ]; what is more, Lb1G04899 participates in salt gland differentiation and responds to salt stress [ 28 ], laying a foundation for further exploration of the effects of bHLH genes in L. bicolor salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is no report on the specific bHLH gene known to regulate salt gland development in other halophyte species, making it difficult to find homologous and unique genes for salt gland development. Most studies about L. bicolor remain at the developmental level of the epidermal structure of heterologous overexpression plants [ 20 , 46–48 ], and there has been little research into the roles of L. bicolor genes in salt gland generation and salt discharge. Earlier, we confirmed by in situ hybridization that the L. bicolor gene Lb1G04899 ( LbbHLH ) is expressed in salt glands [ 29 ]; what is more, Lb1G04899 participates in salt gland differentiation and responds to salt stress [ 28 ], laying a foundation for further exploration of the effects of bHLH genes in L. bicolor salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, more than 800 million hectares of cultivated land are currently harmed by high salinity [ 17 ]. It is estimated that soil salinization will impinge on over 20% of global irrigated farmland by 2050 [ 18 , 19 ], seriously threatening food production and food security [ 20 ]. Enough arable land must be maintained to produce sufficient food to feed the worldwide population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that SWEET genes could be induced by low temperatures and participate in cold stress responses in many plants. For example, the overexpression of DlSWEET1 in the tropic fruit plant longan ( Dimocarpus longan ) improved cold tolerance in transgenic Arabidopsis plants [ 58 ]. BoSWEET2b , BoSWEET4a , and BoSWEET15b were significantly upregulated in the cabbage leaves after cold stress [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its well-known role as a carbon source and building block, sugar serves as an osmotic agent to confer plants resistance to abiotic stress. Two research papers [ 7 , 8 ] elegantly demonstrated the crucial role of the SWEET gene family in the cold tolerance of plants. In Longan ( Dimocarpus longan ), a subtropic fruit tree with high economic value and sensitivity to cold, ref.…”
mentioning
confidence: 99%
“…In Longan ( Dimocarpus longan ), a subtropic fruit tree with high economic value and sensitivity to cold, ref. [ 7 ] carried out a huge study consisting of identifying 20 longan SWEET (referred to as DiSWEET) genes and characterizing their phylogenetic relationships, structures, cis -acting elements and tissue-expression patterns. They found that this transporter family is divided into four clades with conserved motifs and similar exon–intron organization.…”
mentioning
confidence: 99%